Kaolin as a Feedstock for a Versatile Synthesis of Composite MFI/MCM-41 with Enhanced Catalytic Properties - Sosa, Eleida; González, Sergio; Aguirre, Fernando; Rodríguez, Pedro; Uzcátegui, Alvaro; Mora, Andrés; González, Gema; Villarroel, Marlín; Belandria, Lynda; Lugo, Claudio; Férnandez, Jorge (Ciencia, 2015)
Kaolin was used as an efficient and low cost feedstock for the synthesis of MFI/MCM-41 compo-site material, zeolite type MFI and Al-MCM-41, using TPA and CTAB as structure directing agents. First, the MFI was synthesized from kaolin, the obtained MFI was treated with NaOH solutions (1-4M), subsequently the reaction mixture was treated under MCM-41 synthesis conditions and the MFI/MCM-41 composite material was obtained. The materials were characterized by XRD, nitrogen adsorption/desorption isotherms, SEMEDX, TEM and TPD-NH3. The activity, selectivity and catalytic stability were evaluated in the m-xylene transformation reaction. In the absence of alkaline treatment two phases were observed zeolite and mesoporous material. The alkaline treatment partially dissolved the zeolite structure, modifying the characteristic zeolite morphology, reducing its crystal domains and creating mesoporosity. The zeolitisized kaolin treated with 2 or 3M NaOH showed a significantly higher density of strong acid sites than the parent zeolites, therefore with high catalytic activity, with p/o and D/I selectivities similar to that of MCM-41, combining the best of both structures, the MFI high catalytic stability and activity, and the MCM-41 lack of diffusion limitation and the possibility of bulky transition state formation. The alkaline treatment eases zeolite dissolution and leads to the SBU assemble around the surfactant and into the mesoporous walls.